2007
DOI: 10.1111/j.1365-2559.2007.02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Y‐chromosome in gonadal tumours using fluorescence in situ hybridization: diagnostic value in intersex conditions including older patients with clinically unsuspected androgen insensitivity syndrome

Abstract: The demonstration of SRY using FISH is useful in the assessment of gonadal specimens from patients with intersex disorders, particularly in older individuals where the diagnosis may be unsuspected clinically. However, it may be necessary to examine multiple specimens in some cases to confirm the presence of Y-chromosomal material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…Other modes of presentation include a known family history of X-linked complete androgen insensitivity syndrome and, occasionally, the discovery of a pelvic mass arising from a gonadal tumor [7]. No precise figures are available for the prevalence of CAIS, but estimates range from one in 20,400 to one in 99,100 genetic males on the basis of a proven molecular diagnosis [8].…”
Section: Casementioning
confidence: 99%
“…Other modes of presentation include a known family history of X-linked complete androgen insensitivity syndrome and, occasionally, the discovery of a pelvic mass arising from a gonadal tumor [7]. No precise figures are available for the prevalence of CAIS, but estimates range from one in 20,400 to one in 99,100 genetic males on the basis of a proven molecular diagnosis [8].…”
Section: Casementioning
confidence: 99%
“…12 Other modes of presentation include a known family history of X-linked complete androgen insensitivity syndrome and, occasion ally, the discovery of a pelvic mass arising from a gonadal tumour. 13 Adult women with complete androgen insensitivity syndrome are generally taller than women without the syndrome, but are on average shorter than the male population. 14 Patients in whom gonadectomy is delayed are even taller, suggesting a relative oestrogen defi ciency before gonadectomy.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In an earlier study we showed that FISH for the SRY gene was positive in 16/18 paraffin-embedded tissue samples from phenotypic female patients with androgen insensitivity syndrome or gonadal dysgenesis whereas no reaction was seen in 10 patients with sporadic ovarian germ cell or sex cord stromal tumours 2. FISH has the advantage of relative tissue preservation allowing localisation of the signal to the tumour cells.…”
mentioning
confidence: 98%